The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00261-015-0480-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholangiocarcinomas mimicking other lesions

Abstract: Cholangiocarcinomas can be misdiagnosed when they are small and hypervascular. This atypical hypervascular appearance is rare, and may mimic benign liver lesions and other malignant lesions, especially when small. Awareness of the confounding imaging features of these tumors should lead to a more meticulous evaluation of small hypervascular lesions, and may minimize the risk of misdiagnosing early-stage cholangiocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…While lesions with hallmark malignant features can be resected without further evaluation, smaller lesions are often biopsied for confirmation using tissue examination. 19 In our analysis, we chose only to include patients with T1 and T2 tumors. These smaller, more confined lesions are of particular interest as they offer the greatest diagnostic ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…While lesions with hallmark malignant features can be resected without further evaluation, smaller lesions are often biopsied for confirmation using tissue examination. 19 In our analysis, we chose only to include patients with T1 and T2 tumors. These smaller, more confined lesions are of particular interest as they offer the greatest diagnostic ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…The unenhanced MRI findings in our study are in accordance with the conclusions of previous studies. [ 13 15 ] However, it was reported that a target sign in a DWI sequence occurred in approximately 75% (24/32) of cases of small ICC, and DWI is believed capable of distinguishing ICC from HCC. [ 13 ] However, in our study, only approximately one third of the cases had the target sign.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that typical ICC has a different appearance than HCC on contrast-enhanced MRI, [ 1 , 7 , 9 ] a certain percentage of ICCs exhibit atypical imaging features, especially those with diameters ≤30 mm. [ 10 , 11 ] Although some scholars have confirmed that ICCs with different diameters have different imaging features, [ 12 15 ] the MRI enhancement characteristics of small ICCs with varying diameters remain to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Following IV contrast administration, CCs follow an enhancement pattern similar to CECT with little tumoral enhancement on arterial phase images followed by delayed enhancement on delayed phase images. [54][55][56][57][58] The presence of satellite nodules confers a poor prognosis and usually renders a patient inoperable. 59,60 Intraductal CC shows a variety of imaging features depending on its growth characteristics and can manifest on MRI as diffuse infiltrating with severe duct ectasia, an intraductal polypoid-like mass with focal duct dilatation, cast-like lesions, or as a focal stricture.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%